Positive Periodic Solutions for a Class of Strongly Coupled Differential Systems with Singular Nonlinearities - Ruipeng Chen; Guangchen Zhang; Jiayin Liu (Complexity)
This article studies the existence of positive periodic solutions for a class of strongly coupled differential systems. By applying the fixed point theory, several existence results are established. Our main findings generalize and complement those in the literature studies.